Interaction study of moxifloxacin with Cu(II) ion using square-wave voltammetry and its application in the determination in tablets - Trindade, Magno Aparecido Gonçalves; Cunha, Patrícia Alessandra da Cruz; de Araujo, Tatiane Alfonso; da Silva, Glaucia Maria; Ferreira, Valdir Souza (Eclética Química, 2006)
This work presents an electroanalytical method for the determination of moxifloxacin (MOXI) in tablets by its interaction with Cu(II) ion and subsequent electrochemical reduction at hang- ing mercury drop electrode (HMDE). A well-defined reduction peak at -0.21 V vs. Ag/AgCl in Phosphate buffer 0.04 mol L -1 pH 8.0 was observed for the complex reduction MOXI-Cu(II), using square-wave voltammetry (SWV). Using a 10 s of accumulation time at -0.40 V was found a limit detection of 3.60x10 -8 mol l -1 . The obtained results have shown good agreement with those obtained by spectrophotometric method.